Neem Coatted Urrea relevance and IFFCO initiatives - Kallingal, Tomgee; Singh, Hitendra Pratap (Indian Farming, 2017)
It is well established that neem coated urea could prove to be an effective tool to achieve these goals to a considerable extent, without unduly burdening the soil. The benefits of NOCU in terms of better NUE, lower nitrate pollution of under ground water, lesser environmental hazards, lesser carbon foot prints, would all be the catalysts in enhancing the acceptability of NOCU at the farmer’s end. The other benefits like employment opportunities, entrepreneurial avenues,revenue of the neem oil trade, etc. has proved to be an additional incentives at the rural level.